Matharpacady-19.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Matharpacady has a strong historical connection with Goa and Goan Christians. The neighbourhood has several kudds; dormitories that provide accommodation to migrant workers from Goa at a nominal fee. The kudds are managed by clubs linked to villages in Goa, which patronize them. This kudd, 21/B Ground Floor, Matharpacady, is run by the Association of Paroda from Paroda village, in Salcete taluka, South Goa district. It was established in 1900.